Expressing Surprise A Cross-Linguistic Description of Mirativity (Altre Modernità, 2014)
As I have argued elsewhere (Mocini 2009; 2011; 2013), emotions play a decisive role inpromotional discourse. The power of logical argument may not be sufficient toconvince customers. For this reason, writers or speakers usually appeal to theaudience’s emotional response to achieve persuasion. Ekman (1999) claims thatsurprise is one of the basic universal emotions, and only the basic emotions are thereal emotions.1 Following DeLancey (1997; 2001) and other researchers (Dickinson2000; Aikhenvald 2004; Peterson 2010, 2013), we use the term mirativity to refer to thesemantic category employed to mark the fact that some information is new orsurprising.